Push-out bond strength and apical microleakage of (MTA Plus, Biodentine, and Bioceramic) as apical third filling (An in vitro study) (Mustansiria Dental Journal, 2019)
Background: This study was conducted to evaluate the sealing ability of (MTA Plus,Biodentine Bioceramic root repair material) as an apical third filling by using(Push-out bond strength test, apical microleakage test).Materials and methods: Sixty straight palatal roots of the maxillary first molars teethwere used in this study, the roots were instrumented by using crown downtechnique with Protaper universal rotary system, the roots were randomly dividedinto three groups according to the materials used for filling apical third(n=20).Group (1): MTA Plus . Group (2): Biodentine. Group (3): Bioceramicrepair material. For all groups complete obturation with easy & quick obturationsystem was used. After incubation period of three days ten roots for each groupwere embedded in clear acrylic resin and each root sectioned in apical to provideslice 2mm in thickness. The bond strength was measured using computerizeduniversal testing machine. Ten roots remain from each group used for apicalmicroleakage study. The roots submerged in 2% methylene blue for three days.The roots were cleared and the degree of linear dye penetration was measured inmillimeter by stereomicroscope under 40 X magnification with calibrated scaleocular grid. The data were analyzed statistically using ANOVA and LSD test.Results: In push-out bond strength showed the Biodentine has the highest meanvalues (19.687) in comparison with other groups followed by MTA Plus groupwhich the mean value was (19.395), while the BC material group has the lowestmean value (10.977). In microleakage the BC material group has the high meanvalues (0.477) of apical dye penetration in comparison with other groups.Biodentine group has lowest mean values (0.359) of apical dye penetration.Conclusions: The Biodentine higher push-out bond strength and less apicalmicroleakage then other test materials.